Propagation and Focusing Properties of Vortex Beams Based on Light Ray Tracing - Cai, Meng-Qiang; Wang, Qiang; Li, Yong-Nan; Tu, Cheng-Hou (Frontiers in Physics, 2022)
By using the ray-tracing method based on geometric optics, we studied the propagating and focusing characteristics of vortex beams with a top-hat intensity distribution. An intuitive mathematical model is established for the propagating and focusing of vortex beam, revealing the mechanisms and physics underlying the spatial evolution, e.g., the dark spot formation in the center of a vortex beam, the relationship between the radius of the dark spot and the propagation distance, and the rotational angle varying with the propagation distance for an azimuthal asymmetric vortex beam. The experimental observations are consistent with theoretical predictions. The results and findings are helpful to intuitively understand the propagation and evolution of specific vortex beams, thereafter they are of significance for explorations about the novel properties of twisted vortex beams and their applications.